Green accounting in Indonesia pathways to sustainable economic development - Zuhri, Saefudin (Journal of Economics and Business Letters, 2022)
This study examines the implementation and impact of Green Accounting practices in Indonesia, a nation at the crossroads of rapid economic growth and environmental sustainability challenges. Utilizing a mixed-methods approach, the research combines qualitative insights from interviews with policymakers, corporate accountants, environmental NGOs, and academic experts, with quantitative analysis from company surveys and national environmental indicators. The findings reveal a growing awareness and gradual adoption of Green Accounting practices among Indonesian businesses, driven by regulatory pressures, international collaboration, and a burgeoning corporate social responsibility ethos. However, the study also identifies significant barriers to widespread implementation, including technical expertise gaps, regulatory shortcomings, and limited recognition of the long-term economic benefits of environmental sustainability. Despite these challenges, the research underscores the potential of Green Accounting to reconcile economic development with environmental preservation in Indonesia. The study contributes to the discourse on sustainable development by highlighting the importance of regulatory support, capacity building, and mindset shifts towards long-term sustainability. It calls for a concerted effort among stakeholders to overcome existing obstacles and fully realize the benefits of Green Accounting for Indonesia's future.